Formulasi sediaan krim lulur dari sari wortel (Daucus carota L.) sebagai anti aging - Fahma Shufyani; Muhammad Andry; Rida Evalina Tarigan (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background; Carrots are famous for the high beta carotene content in the fruit along with other vitamins, namely vitamin B and vitamin E. Vitamin E's role in the skin includes antioxidant, maintaining skin moisture, sun protection, and wound healing process. As a natural antioxidant, vitamin E is able to counteract free radicals and oxygen molecules. Objective: To find out carrot juice (Daucus carota L.) can be formulated as a scrub cream as anti-aging and to find out at what concentration is the most effective in the preparation of carrotle scrub cream (Daucus carota L.) as anti-aging. Methods: This type of research was conducted experimentally. This research includes collecting respondents, measuring moisture content, smoothness, pores, blemishes, and wrinkles on the skin of respondents, making carrot juice, making scrub preparations from carrotle and evaluating preparation tests. Results: The use of scrub cream preparations containing carrotle (Daucus carota L.) concentration of 15% for 4 weeks showed changes in skin condition for the better with increased water content of 19.3 to 40 (107.25%), smoother skin smoothness of 36.3 to 20.6 (43.25%), shrinking pores 64 to 20.6 (67.81%), many blemishes were reduced 51 to 11.3 (77.97%), wrinkles that were reduced on the respondent's skin showed better results obtained, namely changes in wrinkles 45 to 13.6 with a recovery percent of (69.77%). Conclusion: The conclusion of this study is that carrottle (Daucus carota L.) can be formulated as a scrub cream as anti-aging.